The first 60 cases of robotic sacrocolpopexy with the novel HUGO RAS system: feasibility, setting and perioperative outcomes - Panico, Giovanni; Vacca, Lorenzo; Campagna, Giuseppe; Caramazza, Daniela; Mastrovito, Sara; Lombisani, Andrea; Ercoli, Alfredo; Scambia, Giovanni (Frontiers in Surgery, 2023)
Introduction We present the preliminary report of the first 60 cases of robotic sacrocolpopexy (RSCP) performed with a minimally invasive approach by using the new HUGO RAS system (Medtronic) with the aim of assessing its feasibility, safety and efficacy. Methods Results in terms of operative time, intraoperative blood loss, post-operative pain, length of hospitalisation, intra and post-operative complications were comparable to previously described laparoscopic and robotic techniques. Results Urogynecological assessment at three months follow up showed surgical anatomic success in 96.7% of patients (<2 POP-Q stage), while subjective cure rate was 98.3%. Conclusions This is the first series analyzing RSCP outcomes for POP using the new Hugo RAS system. Our results suggest effectiveness both in objective and subjective outcomes, with minimal intra and post-operative complications. Larger series as well as longer follow-up are needed to better define advantages and possible disadvantages of this novel system. Our work may represent the basis of future studies to confirm its safety, efficacy and feasibility, and may provide technical notes for other centres that wish to perform RSCP through this innovative system.